The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/aac.50.1.279-285.2006
|View full text |Cite
|
Sign up to set email alerts
|

Single-Ascending-Dose Pharmacokinetics and Safety of the Novel Broad-Spectrum Antifungal Triazole BAL4815 after Intravenous Infusions (50, 100, and 200 Milligrams) and Oral Administrations (100, 200, and 400 Milligrams) of Its Prodrug, BAL8557, in Healthy Volunteers

Abstract: BAL8557 is the water-soluble prodrug of a novel antifungal triazole, BAL4815. BAL4815 is active against a broad spectrum of major opportunistic and pathogenic fungi, including strains that are resistant to other azoles. Cohorts of healthy male subjects received single-ascending oral (p.o.) doses of BAL8557 that were equivalent to 100, 200, or 400 mg of BAL4815 or single-ascending, 1-h constant-rate intravenous (i.v.) infusions of BAL8557 which were equivalent to 50, 100, or 200 mg of BAL4815. In each cohort, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
177
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(193 citation statements)
references
References 8 publications
9
177
1
6
Order By: Relevance
“…In studies of healthy volunteers, isavuconazole has been shown to be well tolerated and to have a low clearance, large volume of distribution, high bioavailability, and long elimination half-life (20,31). The present study extends these data to provide PK parameters for two high-and low-dose regimens of i.v.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In studies of healthy volunteers, isavuconazole has been shown to be well tolerated and to have a low clearance, large volume of distribution, high bioavailability, and long elimination half-life (20,31). The present study extends these data to provide PK parameters for two high-and low-dose regimens of i.v.…”
Section: Discussionsupporting
confidence: 55%
“…Available in both i.v. and oral formulations, isavuconazole is the active antifungal component of isavuconazonium sulfate, a water-soluble prodrug that is rapidly and almost completely (Ͼ99%) converted to isavuconazole via plasma esterases (20). The results of in vitro and animal model studies have shown that isavuconazole is active against Candida spp.…”
mentioning
confidence: 92%
“…In plasma, it is rapidly and almost quantitatively (Ͼ99%) converted by esterases to BAL8728 (prodrug cleavage product) and to BAL4815 (active drug) (2). Area under the concentration-time curve (AUC) values of BAL8728 were low and amounted to approximately 1% of the corresponding AUCs of BAL4815 (15). BAL4815 is a potent inhibitor of ergosterol biosynthesis and shows in vitro broad-spectrum activity against all major opportunistic fungi and the true pathogenic fungi.…”
mentioning
confidence: 99%
“…BAL4815 is a potent inhibitor of ergosterol biosynthesis and shows in vitro broad-spectrum activity against all major opportunistic fungi and the true pathogenic fungi. In rat and murine models, BAL4815 was highly effective against systemic candidiasis and aspergillosis First pharmacokinetic data of BAL4815 in human were obtained in a single-ascending-dose study after intravenous and oral administrations (15). As already expected from animal experiments (2), BAL4815 was characterized in healthy subjects by a long elimination half-life (56 to 104 h), a low plasma clearance (1.9 to 5.0 liter/h), and a large volume of distribution (155 to 494 liters).…”
mentioning
confidence: 99%
“…The pharmacokinetic profile of isavuconazole is well described in healthy volunteers. 29,30 Isavuconazole is more than 99% protein bound in serum, has a large volume of distribution (approximately 450 L), and displays an elimination half-life of ~80 -130 hours. 27 To achieve rapid steady state concentrations, the drug is administered as a loading dose of 200 mg every 8 hours for six doses, followed by 200 mg once daily.…”
mentioning
confidence: 99%